Church of England Cathedral, Port of Spain, Trinidad - (:unkn) unknown (The Bonanza, Smith Bros and Co., Trinidad, 2010)
Image depicts the Trinity Cathedral in Port of Spain Trinidad, in the Republic of Trinidad and Tobago. This is a view of the cathedral from inside the south western corner of Woodford Square looking south eastward. In this view, some parts of the building are obscured by trees.
Colour: Shades of blue, Green, Yellow, Brown and Gray; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Anglican church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago